The growth cone: an integrator of unique cues into refined axon guidance - Chauvet, Sophie (Biology Reports Ltd, 2009)
One of the challenges to understanding nervous system development is to establish how a fairly limited number of axon guidance cues can set up the patterning of very complex nervous systems. Most of the recent insights relevant to guidance mechanisms have come from cell biologists focusing on processes and molecular machinery controlling the guidance responses in the growth cone.